The impact of household energy access on socio-economic outcomes in Zambia - Chishimba, Sydney (School of Economics, 2024)
This thesis focuses on evaluating the impact of household energy access on the socio-economic wellbeing of households in Zambia. The thesis consists of four studies that are interrelated to answer the broader objective. All estimations and descriptive statistics in this thesis use the World Bank/ESMAP dataset collected in 2017/2018 on Zambia. Consequently, the first study examines the effect of electrification technology on household socioeconomic outcomes. The study emphasizes the need to understand the differential impact of household adoption of grid versus off-grid (standalone solar home systems) electricity on nonfarm employment, monthly income, and expenditure of the household. Using the Inverse Probability Treatment Weighting estimation strategy, the results reveal heterogeneity in the impacts of the technology used in the electrification programme on household income and expenditure per capita. Therefore, the study observes that, though solar home systems technology offers benefits compared to non-connected, grid electricity offers better effects on household income and expenditure. The second study ditches restrictive traditional binary evaluation of electricity access on users' welfare in favour of the multitier evaluation framework. The study applies the Generalized Propensity Score approach with continuous multivalued treatment (electricity availability). The study estimates the dose-response function (average treatment effect) of the household's exposure to electricity in a typical day. The results confirm that availability of electricity is key to improving household livelihood. The longer the exposure to the electricity service, the higher the likelihood of reduced expenditure on alternative energy sources; the more time the households allocate to working away from home for pay; and the increased probability of being employed in the nonagriculture sector. However, increasing exposure to electricity within and across Tiers does not always improve livelihood as households may have limited productive use of the electricity service. Generally, the policy implication derived from the results is the importance of the duration of household exposure to electricity in the electrification programmes in developing countries. The third study estimates WTP for electricity services among non-connected households given the low rate of electricity access in Zambia. The study further estimates changes in WTP for electricity after introducing credit regimes where households are allowed to pay for extended periods of up to one and two years for grid and solar PV, respectively. Contingent valuation approach is applied with single bounded dichotomous responses. The results reveal that the willingness to pay is positive across the payment periods and technology (grid and solar PV). Further, average willingness to pay increases as payment period of the credit facility rises. However, the average willingness to pay for low-capacity standalone PV solar technology falls below market price in shorter payment periods (below 12 months) while for grid electrification and high-capacity standalone PV solar technology, the average willingness to pay is above the above market price across the payment periods. The results underscore the need to provide electricity beyond lighting for households to engage in economic activities. To accelerate electricity access among nonconnected households, we recommend improving households' access to credit financing or offer 2 subsides for them to pay for connection. Introduction of credit regimes increases households' WTP as it helps to smooth consumption among low-income households. The fourth study is motivated by how gender affects household access to cooking energy solutions and consists of two parts. The first part compares the gendered effects of decision-making on the choice of, and expenditure on cooking energy solutions at the household level. Probit and Heckman selection models are estimated for the household choice of, and expenditure on, cooking energy solutions, respectively. The results suggest that when women have strong bargaining power, the likelihood of choosing and having increased expenditure on improved cooking solutions is relatively high. Women's employment status and educational attainment positively increase their bargaining power in adopting improved cookstove, likelihood of participating in the market and household expenditure on improved energy fuel. The second part of the study assesses gendered effects of household access to improved cooking energy solution across multi-Tiers. The study adopts the Propensity Score with Regression Adjustment approach to estimate the effects of accessing improved cooking energy solutions. The study results suggest that the probability of experiencing reduced respiratory illness in higher Tiers as exposure to improved cooking solutions improves as opposed to lower Tiers (1 vs 0) where differentiated effects are low. Gendered results reveal that women experience reduction in respiratory illness of between 3.5% and 5.5% across the Tiers as exposure to quality of cooking energy solutions improves. For the men, the reduction in respiratory illness is only observed in higher Tiers when men tend to participate in cooking as the quality of access to cooking energy solutions improves. Regarding the overall effect on household time allocation to various activities, the results suggest that time saving improves significantly for cooking (between 16.36 and 43.16 minutes) and fuel collection and preparation (between 18 and 23 minutes) as households transition from traditional to improved cooking energy solutions across Tiers. Furthermore, significant increase in time allocated to studying (between 10 and 30 minutes) and income generating activities (between 22 and 44 minutes) is observed as households transition across the Tiers. Gendered results also reveal that women save more time from cooking and fuel collection and preparation in higher Tiers. Therefore, the transitioning process requires identification of users, decision makers and understanding the benefits of being empowered at household level so that policy formulations and training target the right individuals and avoid formulating gender-blind policies. Effectively, the thesis suggests that Zambia should encourage a mix of grid and off-grid solutions, leverage private energy markets with financing, and empower women for a swift energy transition. Several welfare indicators have been adopted in understanding the effects of electrification technology adoption, availability of electricity services, demand for electricity among nonconnected, and gendered access to cooking energy solutions